Pengembangan E-LKPD Matematika Berbantuan Aplikasi Liveworksheet Pada Materi Bangun Ruang Sisi Datar - Santika, Lia; Mulyono, Dodik; Fitriyana, Nur (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
The purpose of this research is to produce mathematics E-LKPD assisted by liveworksheet application on the material of flat side space building in class VIII SMP Negeri Prabumulih II reaching valid, practical and effective criteria. The method used in this research is the development of the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The type of research used is research development (RD). The data collection techniques used by researchers are interviews, questionnaires and tests. For data collection instruments, namely using questionnaires and tests. The data collection techniques used are qualitative and quantitative techniques. The research data includes three things, namely the results of validation, practicality and effectiveness. Sample selection techniques and how to determine sample size. The method used is using analysis to get theories or writings related to it. Sampling techniques can basically be grouped into two, namely probability sampling and nonprobability sampling. From this study obtained the results of the validation test of language, material, media in the very valid category. The results of the practicality test by users (teachers and students) in the very practical category. While the results of the effectiveness test in the good category. From the three problems above, the mathematics E-LKPD assisted by the liveworksheet application is declared feasible to use in learning mathematics